Environmental controls on pteropod biogeography along the Western Antarctic Peninsula. (15th October 2018) - Thibodeau, P. S.; Steinberg, D. K.; Stammerjohn, S. E.; Hauri, C.
Abstract : Pteropods are abundant zooplankton in the Western Antarctic Peninsula (WAP) and important grazers of phytoplankton and prey for higher trophic levels. We analyzed long‐term (1993–2017) trends in summer (January–February) abundance of WAP pteropods in relation to environmental controls (sea ice, sea surface temperature, climate indices, phytoplankton biomass and productivity, and carbonate chemistry) and interspecies dynamics using general linear models. There was no overall directional trend in abundance of thecosomes, Limacina helicina antarctica and Clio pyramidata, throughout the entire WAP, although L. antarctica abundance increased in the slope region and C. pyramidata abundance increased in the South. High L. antarctica abundance was strongly tied to a negative Multivariate El Niño Southern Oscillation Index the previous year. C. pyramidata abundance was best explained by early sea ice retreat 1‐yr prior. Abundance of the gymnosome species, Clione antarctica and Spongiobranchaea australis, increased over the time series, particularly in the slope region. Gymnosome abundance was positively influenced by abundance of their prey, L. antarctica, during the same season, and late sea ice advance 2‐yr prior. These trends indicate a shorter ice season promotes longer periods of open water in spring/summer favoring all pteropod species. Weak relationships were found between pteropod abundance and carbonate chemistry, and no long‐term trend in carbonate parameters was detected. These factors indicate ocean acidification is not presently influencing WAP pteropod abundance. Pteropods are responsive to the considerable environmental variability on both temporal and spatial scales—key for predicting future effects of climate change on regional carbon cycling and plankton trophic interactions.